Slowing the progression of age-related hearing loss: Rationale and study design of the ASPIRIN in HEARING, retinal vessels imaging and neurocognition in older generations (ASPREE-HEARING) trial - Lowthian, J.; Britt, C.; Rance, G.; Lin, F.; Woods, R.; Wolfe, R.; Nelson, M.; Dillon, H.; Ward, S.; Reid, Christopher; Lockery, J.; Nguyen, T.; et al. (2016)
© 2015. Background: Age-related hearing loss (ARHL) is a leading cause of disability in the elderly. Low-grade inflammation and microvessel pathology may be responsible for initiating or exacerbating some of the hearing loss associated with aging. A growing body of evidence demonstrates an association of hearing loss with cognitive decline. A shared etiological pathway may include a role of inflammation, alongside vascular determinants. The ASPREE-HEARING study aims to determine whether low-dose aspirin decreases the progression of ARHL, and if so, whether this decrease in progression is also associated with retinal microvascular changes and/or greater preservation of cognitive function. Design and methods: A three year double-blind, randomized controlled trial of oral 100. mg enteric-coated aspirin or matching placebo, enrolling 1262 Australians aged =. 70. years with normal cognitive function and no overt cardiovascular disease. The primary outcome is the change in mean pure tone average hearing threshold (decibels) in the better ear, over a 3-year period. Secondary outcomes consist of changes in retinal microvascular indicators, and changes in cognitive function. Participants are recruited from a larger trial, ASPirin in Reducing Events in the Elderly (ASPREE), which is designed to assess whether daily low dose aspirin will extend disability-free life. Discussion: ASPREE-HEARING will determine whether aspirin slows development or progression of ARHL, and will interrogate the relationship between inflammatory and microvascular mechanisms that may underlie the effects of aspirin on ARHL. This study will improve understanding of the patterns of comorbidity with, and the relationships between, aging and ARHL, alongside modeling the impacts of ARHL.